Optimización del sistema productivo de la empresa Distrifrut para el mejoramiento de la productividad. - Quisnancela Saltos, Zoila Dalila. (2021)
Distrifrut is a company located in the province of Pichincha, Quito canton, Guamaní parish, which is dedicated to the distribution of fruits and vegetables, making daily deliveries nationwide, due to the type of company, many of its processes have been carried out manually. and without any type of control or standardization, which leads to a low level of efficiency, therefore, the Distrifrut company does not meet the established goals and objectives. It is necessary to indicate that the company in question lacks the necessary workforce to satisfy the fixed demand, therefore, there is a delay in deliveries to the different entities, loss of time and resources, these problems limit both the company and its workers to have goals and opportunities for personal and professional growth, has even reduced competitiveness, which has highlighted the loss of significant contracts with public and private organizations. Another important factor is the lack of experience on the part of the workers in their jobs, since they do not have a plant staff and make constant contractions due to the absence of the staff, which is why the company does not have a training plan. , to this is added the lack of communication between management and workers caused, delays, mistakes and disorganization at the time of executing tasks such as: classification, preparation or distribution of the product. Of equal importance, the non-existence of inventory leads to a loss of profitability and a non-compliance with their orders, due to the extraction of their products by the staff, in addition to the excess of fruits and vegetables in the warehouses that harms the company economically since its Products break down and can no longer be distributed. Finally, the staff does not use personal protective equipment, which can cause an accident, the company does not have adequate signage, the work spaces are not appropriate for good job performance, due to the poor distribution of work areas, which increase times. unproductive.